Water and cattle shape habitat selection by wild herbivores at the edge of a protected area. (5th March 2018) - Valls‐Fox, H.; Chamaillé‐Jammes, S.; de Garine‐Wichatitsky, M.; Perrotton, A.; Courbin, N.; Miguel, E.; Guerbois, C.; Caron, A.; Loveridge, A.; Stapelkamp, B.; Muzamba, M.; Fritz, H.
Abstract: Understanding the spatiotemporal dynamics of human‐wildlife interfaces is important for the sustainable management of protected areas and wildlife conservation. We investigated the drivers of domestic and wild herbivore habitat selection at the edge of an unfenced protected area adjacent to Hwange National Park, Zimbabwe. We used GPS data to quantify the movement patterns of elephant bulls, buffalo and cattle at multiple scales and according to seasonal changes of surface water availability. Cattle, elephant and buffalo prefer open grassland habitats found close to water but elephant and buffalo avoid cattle differently. During the rainy season, cattle enter the protected area daily; buffalo avoid cattle completely at the home range scale, whereas elephant bulls avoid cattle at finer scales by favoring temporal niche shift. Elephant bulls avoid direct encounters with cattle (or people) during the day but come closer to the boundary and to water at night when cattle are kept in enclosures close to the homesteads. During the dry season, when cattle range further into the protected area in search of forage, buffalo and cattle spatial overlap increases as water dependence takes precedence over avoidance. Elephant bulls range closer to the boundary at night and increase the number of excursions into the Communal Area. Cattle herding creates a buffer zone between wildlife areas and human settlements because wild herbivores strongly avoid livestock and people. However, avoidance only lasts as long as resources are abundant. Our study suggests that long‐term planning of both artificial water provisioning and traditional cattle herding practices could help maintaining spatial segregation and thus mitigate conservation conflicts such as pathogen transmission, crop raiding or livestock depredation. Abstract : We studied cattle, buffalo and elephant movement patterns at the edge of a protected area in Zimbabwe to understand the role of artificial water provisioning and cattle herding on human wildlife coexistence. Wild herbivores avoid cattle and people more strongly during the rainy season when surface water is widely distributed than during the dry season when water dependence outweighs spatiotemporal avoidance. Buffalo mainly rely on spatial avoidance at the home‐range scale, whereas elephant prefer temporal niche shifts by coming closer to the protected area boundary at night. Our study suggests that long term planning of both artificial water provisioning and traditional cattle herding practices could help maintaining spatial segregation and thus mitigate conflicts between protected areas and surrounding agro‐pastoralists.